PERLINDUNGAN HUKUM BAGI KREDITUR SEHUBUNGAN DENGAN COVERNOTE NOTARIS SEBAGAI DASAR PENCAIRAN KREDIT TERKAIT TIDAK DILAKSANAKANNYA ISI COVERNOTE - Prayoga, Muhamad Jati; Yudha Cahya Kumala; Mulyadi, Mulyadi (Journal of Innovation Research and Knowledge, 2026)
The use of Notary Covernote in credit agreements is part of the Notary's efforts to provide legal certainty to Creditors to be able to disburse credit before the creation of the Deed of Grant of Dependent Rights (APHT) is completed and the certificate of dependent rights is issued. This research raises two problems, namely what are the legal consequences of a Notary Covernote as the basis for disbursing credits related to the non-implementation of the contents of the Covernote? and what is the legal protection for creditors against the Notary Covernote as the basis for disbursing credits related to the non-implementation of the contents of the Covernote? By using the theory of Legal Protection Theory, according to Satjipto Rahardjo and the Theory of Agreement, according to the subject. The method used in this study is legal or normative juridical research. It is done by researching literature materials or secondary data only. The research approaches used are the statutory approach, the case approach, the analytical approach, and the conceptual approach. The technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, researching literature materials (books, scientific journals, research report results), and other sources of legal materials. The technique of analyzing legal materials is carried out by conducting legal interpretation (interpretation), Grammatical Interpretation, Systematic Interpretation, and legal construction.